The Effect of Heterogeneity on the Distribution and Treatment of PFAS in a Complex Geologic Environment - McGregor, Rick; Benevenuto, Leticia (Frontiers in Environmental Chemistry, 2021)
Per-and polyfluoroalkyl substances (PFAS) have been identified as emerging contaminants of concern in the environment in a wide variety of media including groundwater. Typically, PFAS-impacted groundwater is extracted by pump and treat systems and treated using sorptive media such as activated carbon and ion exchange resin. Pump and treat systems are generally considered ineffective for the remediation of dissolved phase contaminants including PFAS but instead are considered applicable for plume containment. An alternative to pump and treat is in-situ treatment. The demonstrated use of in-situ treatment for PFAS-impacted groundwater is limited with only colloidal activated carbon (CAC) being shown to effectively attenuate PFAS over short and moderate time periods. Active research topics for the in-situ treatment of PFAS include the effect of heterogeneity on the distribution of the CAC, the lifespan of the CAC itself, the effect of competitive adsorption/absorption, and the effect of other geochemical conditions on the removal process. This study looked at the effect of heterogeneity on the distribution of CAC and subsequent treatment of PFAS at a site with a multiple aquifer system. The site’s geology varied from a silty sand to sand to fractured bedrock with all three units being impacted by PFAS and benzene (B), toluene (T), ethylbenzene (E), and xylene (X). Parameters evaluated included the distribution of the CAC as well as the subsequent treatment of the PFAS and BTEX. Results of groundwater sampling indicated that the PFAS detected within the groundwater were treated effectively to below their respective reporting limits for the duration of the 1-year test in both the silty sand and sand aquifers. The PFAS in the fractured rock aquifer showed a different treatment profile with longer carbon chained PFAS being attenuated preferentially compared to the shorter carbon chained PFAS. These results suggest that competitive sorptive reactions were occurring on the CAC within the fractured rock. Analysis of the unconsolidated aquifer materials determined that direct push injection of the CAC was effective at delivering the CAC to the target injection zones with post-injection total organic carbon (TOC) concentrations increasing by up to three orders of magnitude compared to pre-injection TOC concentrations. Heterogeneity did have an impact on the CAC distribution with higher hydraulic conductivity zones receiving more CAC mass than lower hydraulic conductivity zones.